The CaMKII phosphorylation site Thr1604 in the CaV1.2 channel is involved in pathological myocardial hypertrophy in rats. Issue 1 (1st January 2020) - Li, Jingyuan; Wang, Siqi; Zhang, Jie; Liu, Yan; Zheng, Xi; Ding, Fan; Sun, Xuefei; Zhao, Meimi; Hao, Liying
ABSTRACT: Residue Thr1604 in the CaV 1.2 channel is a Ca 2+ /calmodulin dependent protein kinase II (CaMKII) phosphorylation site, and its phosphorylation status maintains the basic activity of the channel. However, the role of CaV 1.2 phosphorylation at Thr1604 in myocardial hypertrophy is incompletely understood. Isoproterenol (ISO) was used to induce cardiomyocyte hypertrophy, and autocamtide-2-related inhibitory peptide (AIP) was added as a treatment. Rats in a myocardial hypertrophy development model were subcutaneously injected with ISO for two or three weeks. The heart and left ventricle weights, each of which were normalized to the body weight and cross-sectional area of the myocardial cells, were used to describe the degree of hypertrophy. Protein expression levels were detected by western blotting. CaMKII-induced CaV 1.2 (Thr1604) phosphorylation (p-CaV 1.2) was assayed by coimmunoprecipitation. The results showed that CaMKII, HDAC, MEF2 C, and atrial natriuretic peptide (ANP) expression was increased in the ISO group and downregulated by AIP treatment in vitro . There was no difference in the expression of these proteins between the ISO 2-week group and the ISO 3-week group in vivo . CaV 1.2 channel expression did not change, but p-CaV 1.2 expression was increased after ISO stimulation and decreased by AIP. In the rat model, p-CaV 1.2 levels and CaMKII activity were much higher in the ISO 3-week group than in the ISO 2-week group. CaMKII-induced CaV 1.2 channel phosphorylation at residue Thr1604 may be one of the key features of myocardial hypertrophy and disease development.Abbreviations: CaMKII: Ca2+/calmodulin dependent protein kinase II; p-CaMKII: autophosphorylated Ca2+/calmodulin dependent protein kinase II; CaM: calmodulin; AIP: autocamtide-2-related inhibitory peptide; ECC: excitation-contraction coupling; ISO: isoproterenol; BW: body weight; HW: heart weight; LVW: left ventricle weight; HDAC: histone deacetylase; p-HDAC: phosphorylated histone deacetylase; MEF2C: myocyte-specific enhancer factor 2C; ANP: atrial natriuretic peptide; PKC: protein kinase C